2013
DOI: 10.4314/ajtcam.v10i5.7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and sgc-7901 cell inhibition activities of <i>Rhizoma Dioscoreae Bulbiferae</i>. Ethanol extracts.

Abstract: The objective of this research was to study the pharmacology of Dioscorea bulbifera L. on antioxidant and anticancer activity. Alcohol extracts of Dioscorea bulbifera L. were made out by different concentration alcohol; they were tested by Hydroxyl radical scavenging test, reducing capacity test and total antioxidant capacity test. In the anticancer test, MTT test was used to study the inhibition rate. The results told that 70% ethanol extracts could scavenge most DPPH· at 2mg/ml. The rate was 55.2%; 80% ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Studies have shown that extracts of Dioscorea bulbifera inhibit amylase and glucosidase and mediate its anti-hyperglycemic effects [73]. Other medicinal properties reported include cardio-protective, anti-oxidant, and anti-apoptotic properties [75][76][77]. In silico analysis have shown that diosgenin has an affinity to bind to amyloid peptides in monomeric and fibril form and can induce calcium influx in human cortical neuronal cell line [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that extracts of Dioscorea bulbifera inhibit amylase and glucosidase and mediate its anti-hyperglycemic effects [73]. Other medicinal properties reported include cardio-protective, anti-oxidant, and anti-apoptotic properties [75][76][77]. In silico analysis have shown that diosgenin has an affinity to bind to amyloid peptides in monomeric and fibril form and can induce calcium influx in human cortical neuronal cell line [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fraction C altered the weight of spleen and thymus, and the amounts of total leukocytes, lymphocytes and neutrophils in tumour-bearing mice. Diosbulbin B was found to be the major antitumor bioactive component in the extracts and demonstrated anti-tumor effects in the dose-dependent manner at the dosage of 2 to 16 mg/kg without significant toxicity in vivo [35].…”
Section: Madagascarmentioning
confidence: 99%
“…Cytotoxicity test of plant extracts against T47D breast cancer cells using MTT assay was conducted following a previous procedure. 7 A volume of 100 μl suspension of T47D cell line culture containing 1.5 x 104 cells was filled in each well of 96-wells microplates. Plant extracts with a volume ranging from 50 to 400 μg/ml, with the interval of 50 μg/ml were added to the cell culture.…”
Section: Fractionation Of a Potential Extract And The Cytotoxic Activmentioning
confidence: 99%
“…The cytotoxicity of potential fractions against T47D cancer cells were carried out using a standard procedure 7 as described in the previous section.…”
Section: Mtt Assay For the Fractionsmentioning
confidence: 99%
See 1 more Smart Citation